Comparison between three age-stratified cohorts reveals poor prognosis of young patients with tongue carcinoma - Baba, Daisuke; Matsuura, Kazuto; Wakabayashi, Masashi; Morishita, Yohei; Nishiya, Yukio; Okano, Wataru; Tomioka, Toshifumi; Shinozaki, Takeshi; Hayashi, Ryuichi (Frontiers in Oncology, 2022)
Objectives: Investigation of the prognosis of young patients with tongue carcinoma has been the focus of several recent studies aimed at improving future precision treatment. Most studies have been two-cohort investigations comparing young and older patients, who have wide discrepancies in prognosis. Older patients, especially those aged >70 years, often have a poor general condition. This affects the prognosis of the older cohort and accounts for the discrepancies observed in two-cohort studies. Accordingly, in this study, older patients (aged ≥71 years) were separated and compared to young and middle-aged patients. Methods: A total of 257 patients with oral tongue carcinoma referred during 2011–2017 were analyzed. Patients were sorted into young (aged ≤40 years), middle-aged (aged ≥41 and ≤70 years), and older (aged ≥71 years) groups. Overall survival (OS) and disease-free survival (DFS) were compared among the groups. Furthermore, patterns of recurrence rates were compared. Results: Compared with young patients, there was no difference in OS or DFS for older patients (hazard ratio [HR]: 1.2, 95% confidence interval [CI]: 0.5–2.7 and HR: 0.7, 95% CI: 0.4–1.2, respectively) in a multivariate analysis. There was also no difference in OS (HR: 0.6, 95% CI: 0.3–1.3) for middle-aged patients. However, middle-aged patients had low recurrence rates (HR: 0.5, 95% CI: 0.3–0.8). With respect to the recurrence type, middle-aged patients had a low local recurrence rate (HR: 0.3, 95% CI: 0.1–0.7). Conclusion: Three-cohort studies should be conducted to evaluate whether the prognosis of young patients with tongue carcinoma is truly poor in terms of future precision treatment.